呼吸検出装置 (2017)
【課題】安価で装着感が良く高感度な呼吸検出装置を提供することにある。【解決手段】粘着シートを介して被験者の腹部に装着される装置本体１と、この装置本体１と腹部Ａとの間に介挿されるエアバッグ２と、を具え、前記装置本体１は、前記エアバッグ２内の空気の圧力変化に基づき被験者の呼吸を検出して出力する計測ユニット５と、その計測ユニット５に電源を供給する電池６とを有することを特徴とする呼吸検出装置である。【選択図】図１ [Problem] To provide a low-cost breathing detection device with high sensitivity which is comfortable to wear. [Solution] A breathing detection device which comprises a device main body (1) that is mounted on the abdomen of a subject via an adhesive sheet and an airbag (2) that is inserted between the device main body (1) and the abdomen (A), wherein the device main body (1) includes a measurement unit (5) that detects and outputs the subject's breathing on the basis of the change in air pressure in the airbag (2) and a battery (6) that supplies power to the measurement unit (5).